2020
DOI: 10.3847/1538-4357/ab7fa3
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic-Ray-driven Outflows from the Large Magellanic Cloud: Contributions to the LMC Filament

Abstract: In this paper, we build from previous work (Bustard et al. 2018) and present simulations of recent (within the past Gyr), magnetized, cosmic ray driven outflows from the Large Magellanic Cloud (LMC), including our first attempts to explicitly use the derived star formation history of the LMC to seed outflow generation. We run a parameter set of simulations for different LMC gas masses and cosmic ray transport treatments, and we make preliminary comparisons to published outflow flux estimates, neutral and ioniz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 100 publications
(152 reference statements)
3
41
0
Order By: Relevance
“…CR-driven winds are generally denser, colder, and smoother than the thermal supernova-driven outflows (Fig. 2c; e.g., Pakmor et al 2016;Ruszkowski et al 2017;Pfrommer et al 2017;Girichidis et al 2018;Bustard et al 2019;Vijayan et al 2020).…”
Section: Cosmic Raysmentioning
confidence: 94%
“…CR-driven winds are generally denser, colder, and smoother than the thermal supernova-driven outflows (Fig. 2c; e.g., Pakmor et al 2016;Ruszkowski et al 2017;Pfrommer et al 2017;Girichidis et al 2018;Bustard et al 2019;Vijayan et al 2020).…”
Section: Cosmic Raysmentioning
confidence: 94%
“…Cosmic rays are likely an important source of energy in the CGM. In the Milky Way ISM, cosmic-ray energy is roughly in equipartition with thermal and magnetic energies (Ginzburg & Ptuskin 1985;Boulares & Cox 1990), and many recent simulations have shown that cosmic rays launch far-reaching galactic outflows (Uhlig et al 2012;Booth et al 2013;Girichidis et al 2016;Simpson et al 2016;Ruszkowski et al 2017;Bustard et al 2020;Jana et al 2020), altering the phase structure of the CGM (Salem et al 2016;Butsky & Quinn 2018;Buck et al 2020;Ji et al 2020). Galaxy-scale simulations that include cosmic rays find that cosmic-ray pressure may even be the dominant source of pressure in the CGM (Girichidis et al 2018;Ji et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, all currently published simulations of LMC-SMC interactions lack sufficient resolution to capture cloud survival and converged mass growth. This is also true of isolated LMC ram pressure stripping simulations (Salem et al 2015;Bustard et al 2018Bustard et al , 2020. We will discuss the implications of this further in §6.2.…”
Section: Radiative Turbulent Mixingmentioning
confidence: 77%